An investigation of the effects of PICSA on smallholder farmers’ decision-making and livelihoods when implemented at large scale – The case of Northern Ghana - Clarkson, Graham; Dorward, Peter; Osbahr, Henny; Torgbor, Francis; Kankam-Boadu, Isaac (Elsevier, 2019)
Participatory Integrated Climate Services for Agriculture (PICSA) is an approach that has been used to date in 20 countries and benefited tens of thousands of households including over 5000 in Northern Ghana and 75,000 in Rwanda. PICSA involves trained field staff or community volunteers working with groups of farmers and includes farmers: using both historical climate information and forecasts; exploring practical options to address challenges and; using participatory decision making tools to evaluate and plan options for individual farm contexts. A survey of randomly selected farmers and detailed case studies was used in Northern Ghana to investigate the influence of PICSA on farmer’s decision-making, livelihoods, and innovation behaviours. Ninety seven percent of farmers had made changes to their practices (mean of three per farmer), including starting new enterprises and a wide range of management practices. Farmers described positive effects including on income and food security and importantly on wellbeing, and confidence in their abilities to address climate change and variability. In case study interviews farmers clearly explained the rationale for their changes as well as reporting how they actively sought and obtained further technical information and resources. Innovation processes observed are in stark contrast to those associated with linear dissemination of technology models.